The comparative effects of oral creatine supplementation and high protein on muscular strength and body composition - Rahmani-Nia, F.; Rahnama, N.; Garazhian, Y. (International Journal of Sports Science and Engineering, 2008)
The purpose of this study was to examine the effects of 6 weeks of oral creatine supplementation and a high-protein diet on muscular strength and body composition. Thirty-six college athletes (at least 1 year of weight training experience) volunteered to take part in the study. They were randomly assigned to one of four groups: creatine and protein (Cr + Pro, n=9), creatine (Cr, n=9), protein (Pro, n=9), and placebo (P, n=9). They showed no significant difference in their pretest values. Cr consumed 5 g of creatine monohydrate in a flavored sucrose drink four times per day for 6 day. After 6 days, supplementation was reduced to 5 g.d-1.Cr +Pro ingested Cr in a same procedure plus a high protein diet (1.6 g.kg/day).Pro ingested placebo plus a high protein diet (1.6 g.kg /day). Placebo ingested a starched, sucrose drink. 1RM strength of arm flexors, bench press, squat and body composition was measured before and after a 6-wk resistance training program. The subjects trained (3 day.Week-1) with determined training loads. Results showed that body mass and lean tissue mass increased to a greater extent with training in Cr + Pro compared to the other groups, and in Cr compared to P group (p< 0.05). There were no significant changes in percent body fat for groups. Cr + Pro group demonstrated greater improvement in 1RM of squat, bench press and arm flexors than other groups. Also, subjects who supplemented with Cr + Pro had similar increases in 1RM of squat, bench press compared to placebo group (p< 0.05). There were not significant differences between Cr supplementation and high protein diet on muscular strength and body composition.